Evaluation of primary hepatocyte function using 2D or 3D culture method for primary rat hepatocytes - Malgum Lim; Yeongji Kim; Yurianna Shin; Keon Bong Oh; Seongsoo Hwang; Youngim Kim; Tai-Young Hur; Sun A Ock (The Korean Society of Animal Reproduction and Biotechnology, 2016)
There is a growing interest in the application of primary hepatocytes for treatment of liver diseases in humans and for drug development. Several studies have focused on long-term survival and di-differentiation blocking of primary hepatocytes in an in vitro culture system. Therefore, the present study also aimed to optimize an in vitro culture system using primary rat hepatocytes. Primary rat hepatocytes from 6-week-old male Crl:CD rats were isolated using a modified two-step collagenase perfusion. Healthy 3.5 × 106 primary rat hepatocytes were seeded into a 2 dimensional (2D) culture in a 25T culture flask coated with collagen type I or into a 3D culture in a 125-ml spinner flask for 7 days. Production of plasma protein (ALB and TF), apoptosis (BAX and BCL2), and CYP (CYP3A1) related genes were compared between the 2D and 3D culture systems. The 3D culture system had an advantage over the 2D system because of the relatively high expression of ALB and low expression of BAX in the 3D system. However, the level of CYP3A1 did not improve in the 3D culture with and without the presence of a dexamethasone inducer. Therefore, 3D culture has an advantage for albumin production and primary rat hepatocyte survivability, but a low expression of CYP3A1 indicated that primary rat hepatocytes require a high?density culture for stress reduction by continuous flow.